Cross-species validation of conserved miR-504/PDHA1 and miR-500/EGLN2 interactions in sheep oocyte development - Junzheng Zhang; Jie Wang; Hao Li; Keyu Fu; Xu Han; Shuang Ji; Yi Jin (Theriogenology, 2026)

Melatonin ameliorates manganese-induced neurological deficits in mice by inhibiting TXNIP signaling–mediated neuroinflammation and microglial pyroptosis: Role of SIRT6 - Jia Liu; Jixing Liang; Keyu Chen; Kuan Liu; Changjiang Yu; Zhuo Ma; Bin Xu (Journal of Hazardous Materials, 2026)

Bioinspired artificial lipase with engineered hydrophilic microenvironment for oriented substrate binding and structured lipids preparation - Han Liu; Keyu Xing; Shaoyi Yu; Jia Tu; Yanna Jiao; Liguang Xu; Wei Chen; Pei Jia; Zhou Xu (Food Research International, 2026)

Circadian-based individualised protection against inflammation–cancer transition in atrophic gastritis patients - Ceng Shan; Min Guo; Feifan Feng; Xihong Wang; Mohang Li; Weichao Xu; Keyu Jia; Yifei Liu; Yifan Jia (EPMA Journal, 2026)

Mineralization of calcium phosphate regulated by a Zr-based MOF on its surface for the removal of beryllium from Be-containing wastewater - Xu Zhao; Zhengyang Shan; Keyu Zhu; Yige Sun; Qingliang Wang; Xiujuan Feng (Chemical Engineering Journal, 2026)

Angstrom confined ion transport in graphene oxide membranes enables highly reversible zinc anodes - Lin Huang; Yihao Xu; Teng Deng; Shu Liu; Liping Chen; Yonghong Fu; Lei Dong; Juan Wang; Keyu Xie (Chemical Engineering Journal, 2026)

From built-in LiDFP to high-stability interface: A targeted and persistent multistage strategy for lithium-rich cathode - Jin Zhu; Xiaosong Zhang; Denghui Ma; Lei Zhang; Yiyao Xiao; Keyu Zheng; Jiamin Duan; Shunjie Xu; Longhao Cao; Yinghui Li; Guanghua Guo; Xiuxia Zuo; et al. (Chemical Engineering Journal, 2026)

The MPOA-VTA Pathway: From Pup Care to Adult Helping - Keyu Chen; Jingkai Fan; Han Xu (Neuroscience Bulletin, 2026)

Noteworthy roles of autotrophic carbon fixation in a semiarid farmland soil - Zicun ZHENG; Zhen LIU; Fang KANG; Boyuan LIU; Jing XU; Xiang FANG; Lang LIU; Keyu FA (Pedosphere, 2026)

Engineering a 2-methylimidazole framework nanozyme for efficient oxidation of lactose to lactobionic acid under mild conditions - Donghui Xie; Yanna Jiao; Shaoyi Yu; Jia Tu; Yunhui Cheng; Xiaohong He; Daichen Mu; Keyu Xing; Zhou Xu (Journal of Environmental Chemical Engineering, 2026)

Bacillus Cereus C3 Addition Facilitates Carbohydrate Degradation and Earthworm Growth During Vermicomposting of Sewage Sludge - Tiantian Tian; Xinge Cui; Wenxing He; Keyu Liu; Jiran Zhang; Shimin Zhang; Xitian Yang; Kun Wu; Xianqin Jiao; Shuxia Xu (Water, Air, & Soil Pollution, 2026)

Grazing-induced enhancement of rhizosphere effect on soil multifunctionality is linked to altered microbial life-history strategies in semiarid grasslands - Nuo Xu; Le Li; Yuhong Luo; Yunxiang Jin; Keyu Bai; Qiuli Bao; Jiahui Liu; Yufan Bao; Yuchun Yan (Agriculture, Ecosystems & Environment, 2026)

Research trends and hotspots of microalgae protein as a functional ingredient in plant-based foods: A bibliometric analysis based on the web of science - Jiayi He; Haoxie Xu; Keyu Lu; Chunli Guo; Ming Du; Ruochen Jia (Algal Research, 2026)

Apoptotic extracellular vesicles: unveiling mechanisms, diverse functions, and biomedical implications - Xuan Li; Keyu Wang; Caining Wen; Haorui Li; Limei Xu; Yuanmin Zhang; Xiao Xu; Yujie Liang (Apoptosis, 2026)

The Role of Coagulation-Related Genes in Glioblastoma: A Comprehensive Analysis of the Tumor Microenvironment, Prognosis, and Treatment - Jingyi Yang; Lei Shen; Yuankun Cai; Ji Wu; Keyu Chen; Dongyuan Xu; Yu Lei; Songshan Chai; Nanxiang Xiong (Biochemical Genetics, 2026)

Synergistic pathways for regional energy transition and water conservation: insights from the receiving areas of the South-to-North Water Diversion Middle Route - Weiwen Liu; Chao Ma; Haixing Gou; Ximeng Xu; Ruixin Zhang; Weiren Huang; Keyu Guo (Journal of Hydrology, 2026)

Salt barriers produce optimal effects in increasing crop yield and reducing salinity in semi-arid and coastal areas compared to other regions: A meta-analysis - Lang Liu; Fang Kang; Jing Xu; Zhen Liu; Huarui Gong; Ziyang He; Keyu Fa (Field Crops Research, 2026)

Exogenous melatonin regulates hormone metabolism involved in delaying the ripening process in cherry tomato fruit during storage - Hang Zhang; Yue Wang; Jianhui Cheng; Wenbo Lei; Keyu Xu; Lilai Yin; Chen Huan; Shuling Shen; Lanying Yao; Xiaolin Zheng (Postharvest Biology and Technology, 2025)

Fiber-regulated vibration suppression and mechanical behavior of CFRP corrugated channel cored sandwich structures - Jiaming Sun; Yanlong Xu; Keyu Zhu; Leilei Yan; Xitao Zheng; Zhichun Yang (Engineering Structures, 2025)

Environmental preferences and interspecific interactions of autotrophic microorganisms in dryland agroecosystems soils - Boyuan Liu; Fang Kang; Zicun Zheng; Lang Liu; Jing Xu; Ziyang He; Keyu Fa (Applied Soil Ecology, 2025)

Motif-based structural analysis and resilience assessment of the RCEP shipping network - Keyu Xu; Jiaguo Liu; Yating Fu (Ocean & Coastal Management, 2025)

Dynamic interactions in energy-water nexus: risk-based framework for balancing electricity expansion and water resource sustainability - Haixing Gou; Chao Ma; Ximeng Xu; Weiwen Liu; Ruixin Zhang; Weiren Huang; Keyu Guo (Journal of Hydrology, 2025)

Metagenomic analysis of bacterial fitness and plasmids carrying blaTEM-1 and virulence genes before and after cleaning and disinfection in pig slaughterhouses - Shanshan Chu; Yan Chen; Zhuoqun Xu; Jie Zhou; Keyu Li; Qi Zhang; Min Qian; Jianzhong Han; Daofeng Qu (Journal of Hazardous Materials, 2025)

Phenotypic and transcriptomic insights into the antibacterial effects of magnolol against the novel pathogen Vibrio misgurnus - Keyu Zhou; Qibin Jiang; Bowen Huang; Kun Peng; Mingqi Ai; Le Xu; Songmao Wu; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Aquaculture International, 2025)

Straw humification coefficient and its relation to soil carbon and nitrogen status - Yue Sun; Huiying Wang; Wei Jia; Keyu Ren; Bingjie Li; Hongqin Zou; Yinghua Duan; Minggang Xu (Journal of Environmental Management, 2025)

Myricetin, as a potential new antiviral agent against Rana grylio ranavirus (RGRV) - Kun Peng; Silu Tian; Le Xu; Yu Yuan; Mingqi Ai; Qibin Jiang; Keyu Zhou; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Fish & Shellfish Immunology, 2025)

Excessive mitochondrial stress response triggers neuronal injury through the persistent eIF2α phosphorylation in mice exposed to manganese - Yunfei Jia; Bin He; Keyu Chen; Kuan Liu; Changjiang Yu; Bo Sun; Zhuo Ma; Bin Xu (Journal of Hazardous Materials, 2025)

SiO2-assisted co-assembly of ultrafine aramid nanofiber-based porous thermal-resistant separator for Lithium-ion batteries - Fuhai Guo; Minghan Xu; Shi Feng; Keyu Zhang; Xiaotong Zheng; Hao Xue; Fulan Hao; Rui Zhuang; Qingchun Liu; Lei Zhang; Jianjun Zhang; Qingfu Wang (Chemical Engineering Journal, 2025)

Feldspar dissolution rates and controlling factors under near-equilibrium conditions in subsurface settings - Jinhao Xu; Guanghui Yuan; Yingchang Cao; Zihao Jin; Keyu Liu (Science China Earth Sciences, 2025)

p-chlorophenylalanine treatment accelerates tomato fruit ripening through hormone synthesis and glycolytic pathway during storage - Keyu Xu; Ran Yan; Hang Zhang; Lilai Yin; Wenbo Lei; Jianhui Cheng; Chen Huan; Yan Liu; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2025)

Sensitive lateral flow immunoassay enabled by signal amplification strategy with high active oxidase-like nanozymes - Jie Zhu; Yunhui Cheng; Xufeng Wang; Hao Wu; Ye Jiao; Keyu Xing; Li Yao; Pei Jia; Zhou Xu (Food Bioscience, 2025)

Construction and characterization of probiotic intestinal-targeted delivery system based on complex coacervation and double-emulsion structure - Nuocheng Xu; Yutong Feng; Huiping Wan; Zilong Li; Keyu Sun; Shuhong Ye (Food Hydrocolloids, 2025)

Impact of landform on Spatial-Temporal distribution and Scenario-Based prediction of carbon stocks in arid Regions: A Case study of Xinjiang - Keyu Song; Weiming Cheng; Baixue Wang; Hua Xu (CATENA, 2025)

PAD resin: An intelligent adsorbent for solving Cr(VI) pollution with real-time feedback and high efficiency - Yuanhao Wang; Guihong Lan; Haiyan Qiu; Keyu Pu; Xiangming Liu; Ling Chen; Bo Xu (Journal of Hazardous Materials, 2025)

Ferric uptake regulator (Fur) in Vibrio mimicus acts as an activator of citrate cycle and oxidative phosphorylation pathways, while enhancing virulence potential - Kun Peng; Keyu Zhou; Qibin Jiang; Yilin Wang; Mingqi Ai; Le Xu; Jiao Wang; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Aquaculture, 2025)

3D reconfigurable hydroxylated carbon nanotubes-based water evaporators with long-distance transportation for continuous vapor generation - Youqiang Huang; Pengjie Zhong; Ningning Zhu; Yinyan Li; Zhen Xiao; Keyu Han; Beibei Xu; Shiqing Xu; Gongxun Bai (Chemical Engineering Journal, 2024)

LNP-mRNA delivers TNF-α antibody to deep cartilage and protects against osteoarthritis - Baixing Li; Lei Cui; Keyu Kong; Yichuan Pang; Yan Chen; Shuning Zhang; Fangfang Wang; Tangjun Zhou; Yunfeng Hua; Mi Cao; Hongtao Xu; An Qin; et al. (Chemical Engineering Journal, 2024)

Development of a CRISPR/Cas12a-based method to detect invasive aquatic species - Minlin Zhang; Xiaoling Zuo; Jiantao Liang; Keyu Lu; Liyun Wei; Xu Yan; Huihong Zhao; Songyong Gan; Jinhui Wu; Qing Wang (Aquaculture, 2024)

Wind erosion prevention and trans-boundary ecosystem service payments in the Hunshandake region - Mengdong Huang; Yu Xiao; Changshun Zhang; Lin Zhen; Keyu Qin; Jingya Liu; Jie Xu; Shuang Gan; Jia Liu; Chunxia Lu; Gaodi Xie (Journal of Cleaner Production, 2024)

Effects of seasoning addition and cooking conditions on the formation of free and protein-bound heterocyclic amines and advanced glycation end products in braised lamb - Qiaochun Chen; Keyu Lu; Jiayi He; Qian Zhou; Siqian Li; Hui Xu; Yuting Su; Mingfu Wang (Food Chemistry, 2024)

A novel magnetic resonance tuning-magnetic relaxation switching sensor based on Gd-MOF/USPIO assembly for sensitive and convenient aflatoxin B1 detection - Shiqin Dai; Keyu Xing; Yanna Jiao; Shaoyi Yu; Xingyu Yang; Li Yao; Pei Jia; Yunhui Cheng; Zhou Xu (Food Chemistry, 2024)

The fundamentals, progress, and perspectives of transition-metal dichalcogenides (TMDs) applied in advanced oxidation processes - Hao Huang; Mengyang Zhang; Keyu Xu; Yanling Zhuang; Yue Li; Longlu Wang (Chemical Engineering Journal, 2024)

Variations and causes of in-situ stress orientations in the Dibei-Tuziluoke Gas Field in the Kuqa Foreland Basin, western China - Guoding Yu; Keyu Liu; Kelai Xi; Xianzhang Yang; Jing Yuan; Zhenping Xu; Lu Zhou; Shaoyong Hou (Marine and Petroleum Geology, 2023)

Seasonal peak and the role of local weather in schizophrenia occurrence: A global analysis of epidemiological evidence - Jihong Hu; Yufan Feng; Hong Su; Zhiwei Xu; Hung Chak Ho; Hao Zheng; Wenyi Zhang; Junwen Tao; Keyu Wu; Mohammad Zahid Hossain; Yunquan Zhang; Kejia Hu; et al. (Science of The Total Environment, 2023)

Target-triggered Fe3O4@NPC-UCNPs assembly for photoactivatable biosensing of Aflatoxin B1 - Zhou Xu; Shaoyi Yu; Xinyi Xie; Qingxia Li; Li Ding; Maolong Chen; Jia Tu; Keyu Xing; Yunhui Cheng (Chemical Engineering Journal, 2023)

Achieving high yield and nitrogen agronomic efficiency by coupling wheat varieties with soil fertility - Keyu Ren; Minggang Xu; Rong Li; Lei Zheng; Huiying Wang; Shaogui Liu; Wenju Zhang; Yinghua Duan; Changai Lu (Science of The Total Environment, 2023)

Stability and energy consumption analysis of arctic fleet: modeling and simulation based on future motion of multi-ship - Keyu Xu; Jiaguo Liu; Hui Meng (Environmental Science and Pollution Research, 2023)

Differential hydrocarbon generation and evolution of typical terrestrial gas-prone source rocks: An example from the Kuqa foreland basin, NW China - Jianliang Liu; Xianzhang Yang; Keyu Liu; Zhenping Xu; Kun Jia; Lu Zhou; Hongxing Wei; Liang Zhang; Shaojun Wu; Xinzhuo Wei (Marine and Petroleum Geology, 2023)

Creating aligned porous structure with cobweb-like cellulose nanofibrils in MXene composite aerogel for solar-thermal desalination and humidity response - Mingqi Ding; Wenjie Ma; Pengju Liu; Jingbo Yang; Keyu Lan; Dawei Xu (Chemical Engineering Journal, 2023)

A systematic review and meta-analysis of air pollution and angina pectoris attacks: identification of hazardous pollutant, short-term effect, and vulnerable population - Min Yang; Keyu Wu; Qiyue Wu; Cunrui Huang; Zhiwei Xu; Hung Chak Ho; Junwen Tao; Hao Zheng; Mohammad Zahid Hossain; Wenyi Zhang; Ning Wang; Hong Su; et al. (Environmental Science and Pollution Research, 2023)

Abnormal ambient temperature change increases the risk of out-of-hospital cardiac arrest: A systematic review and meta-analysis of exposure types, risk, and vulnerable populations - Qiyue Wu; Min Yang; Keyu Wu; Hong Su; Cunrui Huang; Zhiwei Xu; Hung Chak Ho; Hao Zheng; Wenyi Zhang; Junwen Tao; Thi Anh Thu Dang; Mohammad Zahid Hossain; et al. (Science of The Total Environment, 2023)

Carbazole and polyhalogenated carbazoles in the marine environment around the Zhoushan Archipelago: Distribution characteristics, environmental behavior, and sources - Zhaochao Deng; Songtao Hu; Leiming Tang; Lingbo Jiang; Junyu He; Keyu Shen; Yongjiu Xu; Rijin Jiang; Tiejun Li; Chunlei Chen; Bairu Chen; Hanghai Zhou; et al. (Journal of Hazardous Materials, 2023)

Towards Realizing Intelligent Coordinated Controllers for Multi-USV Systems Using Abstract Training Environments - Sulemana Nantogma; Keyu Pan; Weilong Song; Renwei Luo; Yang Xu (Journal of Marine Science and Engineering, 2021)
Unmanned autonomous vehicles for various civilian and military applications have become a particularly interesting research area. Despite their many potential applications, a related technological challenge is realizing realistic coordinated autonomous control and decision making in complex and multi-agent environments. Machine learning approaches have been largely employed in simplified simulations to acquire intelligent control systems in multi-agent settings. However, the complexity of the physical environment, unrealistic assumptions, and lack of abstract physical environments derail the process of transition from simulation to real systems. This work presents a modular framework for automated data acquisition, training, and the evaluation of multiple unmanned surface vehicles controllers that facilitate prior knowledge integration and human-guided learning in a closed-loop. To realize this, we first present a digital maritime environment of multiple unmanned surface vehicles that abstracts the real-world dynamics in our application domain. Then, a behavior-driven artificial immune-inspired fuzzy classifier systems approach that is capable of optimizing agents’ behaviors and action selection in a multi-agent environment is presented. Evaluation scenarios of different combat missions are presented to demonstrate the performance of the system. Simulation results show that the resulting controllers can achieved an average wining rate between 52% and 98% in all test cases, indicating the effectiveness of the proposed approach and its feasibility in realizing adaptive controllers for efficient multiple unmanned systems’ cooperative decision making. We believe that this system can facilitate the simulation, data acquisition, training, and evaluation of practical cooperative unmanned vehicles’ controllers in a closed-loop.